Out of nowhere [large type] - Brown, Sandra, 1948- (Grand Central Large Print, 2023)
"At a Texas county fair, amidst carousels and a bustling midway, children's book author Elle Portman is enjoying a rare night out with her favorite cowboy: her two-year-old son, Charlie. But just as they're about to head home, the unthinkable happens- a shooter opens fire into the crowd, causing widespread panic to erupt all around them. Also caught in the melee was corporate consultant Calder Hudson. Arrogant, self-centered, and high off his latest career win, he's frustrated and confused when he wakes up in the hospital after undergoing emergency surgery on his arm. The doctor tells him that he was lucky--that as far as gunshot wounds go, he pulled through remarkably well. Others weren't so lucky, which instills in Calder a furious determination to get justice... a goal shared by Elle. Their chance encounter at the police station leads to a surprising and inexplicable gravitation to one another, but even as the attraction grows, Elle and Calder can't help but wonder if the unimaginable tragedy that brought them together is too painful and too complicated to sustain-especially while the shooter remains at large"--